Fluconazole and voriconazole susceptibility in oral colonization isolates of Candida spp. in HIV patients. / Susceptibilidad a fluconazol y voriconazol en aislados orales de Candida spp. en pacientes con VIH. - Brito, Daniela; Fernández, Johelia; Castillo, María Andrea; Azuero, Sandra; Hernández-Valles, Rosaura; Saúl-García, Yotsabeth; Valero, Nereida; Villalobos, Rafael; Semprún-Hernández, Neomar; Martínez-Méndez, Dilia (Investigación Clínica, 2020)
Abstract. The identification of Candida species and their antifungal susceptibility is important for the treatment of infected patients. The aim was to determine the susceptibility to fluconazole and voriconazole in isolates from oral colonization of Candida spp. in HIV patients. From the 135 patients studied, 33.3% were females and 66.7% males, with a mean age of 36.6 years and 83.7% of them were under treatment. The identification of the specie was performed by the API20CAUX® test and the antifungal susceptibility was determined by the disc diffusion test. Strains of C. parapsilosis and C. krusei were used as quality controls. The Candida species identificated were: C. parapsilosis complex 52%, C. albicans complex 36% and C. famata 12%. 60% of the isolates were susceptible to fluconazole and 40% were dose-dependent. All were susceptible to voriconazole. In this study, none of the patients had oropharyngeal candidiasis however, 18.5% had Candida spp. colonization, this percentage being below other studies in HIV carriers. We found a high proportion of nonalbicans species but no difference in the CD4+ counts between patients. Resumen. Identificar las especies de Candida y la susceptibilidad a los antifúngicos es importante para el tratamiento adecuado de pacientes infectados. El objetivo fue determinar la susceptibilidad a fluconazol y voriconazol de Candida spp. en aislados de colonizaciones orales en pacientes con VIH. La identificación se realizó mediante la prueba API20CAUX® y la prueba de difusión de disco para la sensibilidad a los antifúngicos. Se utilizaron cepas de C. parapsilosis y C. krusei como control de calidad. De los 135 pacientes, el 33,3% eran mujeres y el 66,7% hombres con una edad media de 36,6 años y el 83,7% recibían tratamiento. Las especies de Candida identificadas fueron: complejo C. parapsilosis 52%, complejo C. albicans 36% y C. famata 12%. La susceptibilidad al fluconazol 60% eran susceptibles y 40% dependía de la dosis. Todas eran susceptibles al voriconazol. En este estudio, ninguno tenía candidiasis orofaríngea, sin embargo, el 18.5% tenía colonización por Candida spp., aunque el porcentaje está por debajo de otros estudios en portadores de VIH. Encontramos una alta proporción de especies no-albicans. No hubo diferencias en el recuento de CD4+ entre los pacientes